Height and Risk of Gestational Diabetes Mellitus: Results from the Healthy Baby Cohort Study - Hui Li; Lulu Song; Lijun Shen; Bingqing Liu; Xiaoxuan Zheng; Lina Zhang; Youjie Wang; Zhongqiang Cao; Shunqing Xu (Journal of Diabetes Research)
Background. The aim of this study was to examine the association between height and plasma glucose level, as well as risk of GDM among Chinese women. Methods. A total of 6941 pregnant Chinese women were recruited from the Healthy Baby Cohort study in Hubei Province, China, in 2012–2014. Measured height was categorized into four groups according to the quartile distribution (≤158.0 cm, 158.1–161.0 cm, 161.1–164.0 cm, and >164.0 cm). GDM was defined based on the International Association of the Diabetes in Pregnancy Study Group criteria. Linear regression was used to estimate the association between height and plasma glucose levels. Logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for the association between height and GDM. Results. The prevalence of GDM was 14.7% in our study. Height was inversely associated with the 1 h and 2h plasma glucose levels (all P value for trend < 0.05), but not with fasting plasma glucose levels. A significant negative trend was found between height and risk of GDM (P value for trend < 0.05), and each centimeter increase in height was associated with 2% (OR: 0.98; 95% CI: 0.96, 0.99) lower risk of GDM. Women in the highest quartile of height (>164.0 cm) had 23% (OR: 0.77; 95% CI: 0.64, 0.94) lower risk of developing GDM than those in the shortest quartile of height (≤158.0 cm), after adjusting for potential confounders. Conclusions. Our findings suggested that height was negatively associated with risk of GDM among Chinese women. The difference in plasma glucose levels is present in the 1 h and 2 h plasma glucose, but not with fasting plasma glucose.